Difference in vertical jumping abilities, endurance and quickness of regeneration lower extremity muscle groups after physical effort between CrossFit and climbing athletes - Gawda, Piotr; Ginszt, Michał; Smołka, Jakub; Paćko, Michał; Skublewska-Paszkowska, Maria; Łukasik, Edyta; Majcher, Piotr (Polish Journal of Public Health, 2018)
Introduction. Productive sporting performance in various sports disciplines often heavily depends on jumping abilities as well as on lower limb muscles power and endurance of the athletes involved. Both CrossFit, a popular high-intensity training program and sport climbing require lower extremity muscular power and endurance. Aim. The aim of this study was to compare vertical jumping abilities, endurance and quickness of the regeneration in gastrocnemius lateralis (GL), vastus medialis (VMO) and gluteus maximus (GM) muscles in CrossFit athletes and sport climbers. Material and methods. The study comprised 20 male athletes aged 24.3±4.7, divided into two equal groups: training CrossFit (CF) and sport climbers (SC). Vertical jump test was recorded by Vicon® motion capture system and AMTI® biomechanics force platforms. The myoelectric activity of the GL, VMO and GM muscles was recorded by myon®. Results. Significant difference in height of vertical jump in CrossFit athletes and sport climbers was observed (SC: 125.43 cm, 120.92 cm; CF: 110.42 cm, 110.86 cm; p<0.05). The endurance of the GL muscles in athletes using CrossFit training is significantly higher in comparison to sport climbers. Athletes training CrossFit have a better ability to recover GL, GM and VMO muscles than sport climbers. Conclusions. Sport climbers have better results in vertical jump tests than the athletes doing CrossFit. The endurance of the GL muscles in athletes doing CrossFit is higher in comparison to sport climbers. Athletes doing CrossFit have also better ability to muscles recover than sport climbers.